Root Responses to Boron Deficiency Mediated by Ethylene - González-Fontes, Agustín; Herrera-Rodríguez, M. B.; Martín-Rejano, Esperanza M.; Navarro-Gochicoa, M. T.; Rexach, Jesús; Camacho-Cristóbal, Juan J. (Frontiers in Plant Science, 2016)
Low boron (B) supply alters the architecture of the root system in Arabidopsis thaliana seedlings, leading to a reduction in the primary root growth and an increase in the length and number of root hairs. At short-term (hours), B deficiency causes a decrease in the cell elongation of the primary root, resulting in a lower growth. Experimental approaches using ethylene insensitive Arabidopsis mutants, inhibitors of ethylene response, and GUS reporter lines suggest that ethylene is involved in these responses of the primary root to B deficiency. Furthermore, it has been shown that auxin participates in the inhibition of cell elongation under short-term B deprivation. These results support that an interaction between ethylene and auxin plays an important role in controlling the primary root elongation, in which a number of genes related to the synthesis, transport, and signaling of both phytohormones could modulate this effect. Evidence for a root cross-talk among both hormones and other possible intermediates (abscisic acid, calcium sensors, and reactive oxygen species) in response to B deficiency is provided and discussed.